Application of "coordinative effect" into tri-solvent MEA+BEA+AMP blends at concentrations of 0.1 + 2 + 2∼0.5 + 2 + 2 mol/L with absorption, desorption and mass transfer analyses. (May 2021) - Shi, Huancong; Cui, Mingqi; Fu, Junxing; Dai, Wenhao; Huang, Min; Han, Jinjin; Quan, Luoqiu; Tontiwachwuthikul, Paitoon; Liang, Zhiwu
Graphical abstract: Highlights: A new idea of solvent improvement with adoption of "coordinative effect" of MEA/RR'NH into MEA/BEA. Blending MEA/RR'NH at small ratio can enhance CO2 absorption and desorption simultaneously. The optimized blending ratio of MEA/BEA + AMP was 0.3 + 2 + 2 among 5 solvents at both absorption and desorption sides consistently. The 0.3 + 2 + 2 mol/L MEA + BEA + AMP has the best performance, and better than 2 + 2 BEA + AMP. The mass transfer performance was conducted on MEA + BEA + AMP tri-solvents (A + B+C), while most peer researches focused on single and bi-solvents (A + B). Abstract: The "coordinative effect" was discovered in MEA + DEA solvents in 2018 via CO2 absorption, and it could enhance both CO2 absorption & desorption within MEA + RR'NH solvents. This study expanded the scope out of MEA + DEA and implemented it by blending MEA into BEA(RR'NH)+AMP solvents. The CO2 absorption, desorption and mass transfer performance were evaluated onto MEA + BEA + AMP (0.1 + 2 + 2∼0.5 + 2 + 2 mol/L) in the batch reactor, recirculation process, and lab-scale absorber with DX structured packing and compared with BEA + AMP (2 + 2 mol/L). The CO2 absorption-desorption parameters were adopted to analyze the coordinative effects. Then, the mass transfer of these 5 tri-solvents were tested by overall mass transfer coefficient ( KG a v ) to evaluate the gas-liquid interactions in an industrial CO2 absorber. The results indicated that the "coordinative effect" of MEA + RR'NH resulted in superior performance of MEA + BEA + AMP (0.3∼0.4 + 2 + 2) over BEA + AMP (2 + 2) on both CO2 absorption and desorption sides, contrary to the conventional concept that MEA enhances absorption but deteriorates desorption of amine blends.